Synthesis of isoprenoid bisphosphonate ethers through C–P bond formations: Potential inhibitors of geranylgeranyl diphosphate synthase - Zhou, Xiang; Reilly, Jacqueline E.; Loerch, Kathleen A.; Hohl, Raymond J.; Wiemer, David F. (Beilstein Journal of Organic Chemistry, 2014)
A set of bisphosphonate ethers has been prepared through sequential phosphonylation and alkylation of monophosphonate ethers. After formation of the corresponding phosphonic acid salts, these compounds were tested for their ability to inhibit the enzyme geranylgeranyl diphosphate synthase (GGDPS). Five of the new compounds show IC50 values of less than 1 μM against GGDPS with little to no activity against the related enzyme farnesyl diphosphate synthase (FDPS). The most active compound displayed an IC50 value of 82 nM when assayed with GGDPS, and no activity against FDPS even at a 10 μM concentration.
Keywords: bisphosphonate; isoprenoid biosynthesis; organophosphorous; phosphonate formation